Comparison between microwave ablation and radiofrequency ablation for treating symptomatic uterine adenomyosis - Xiao Liang Lin; Ning Hai; Jing Zhang; Zhi Yu Han; Jie Yu; Fang Yi Liu; Xue Juan Dong; Ping Liang (International Journal of Hyperthermia, 2020)
Objectives To prospectively compare the effectiveness and safety of percutaneous microwave ablation (PMWA) and ultrasound-guided radiofrequency ablation (USgRFA) for treating symptomatic uterine adenomyosis. Methods One hundred and thirty-three women with symptomatic uterine adenomyosis who met the inclusion criteria were enrolled in our study from October 2015 to October 2017. Sixty-eight patients underwent PMWA, and sixty-five patients underwent USgRFA. All patients were followed up for 12 months. Assessment endpoints included treatment time, percentage ablation, percentage uterine regression, symptom severity scores (SSSs), dysmenorrhea scores and adverse events. Results The mean age of the patients in our study was 39.4 ± 4.2 years (range, 35–50 years), and the median volume of uterine adenomyosis was 124.3 cm3 (range, 28.7–374.5 cm3). The mean ablation time was 16.3 ± 4.9 min (range, 5–23 min) in the MWA group, which was demonstrably superior to that of the RFA group, which was 37.5 ± 6.2 min (range, 5–39 min). The mean percentages of ablation of uterine adenomyosis were 79.7 ± 15.1% and 79.2 ± 14.2% in the MWA group and the RFA group, respectively, and showed no significant difference between the groups. The percentages of regression of uterine volume also showed no marked difference between the two groups. Changes in the dysmenorrhea scores and the SSSs after ablation were similar in the MWA group and in the RFA group, and no significant difference was found between the groups. Finally, the percentage occurrence of adverse events was the same in the two groups. Conclusions The safety and effectiveness of PMWA and USgRFA in the treatment of uterine adenomyosis were similar; however, the mean ablation time of PMWA was shorter than that of USgRFA.